Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Berkarir Sebagai Akuntan Publik (Studi Empiris Mahasiswa Akuntansi di Malang) - Debrina, Helvy Meisya; Junaidi, Junaidi; Mawardi, M. Cholid (Universitas Islam Malang, 2024)
This investigates points to look at the components that impact bookkeeping students intrigued in seeking after a career as a open bookkeeper. sex, internship involvement, subjective standards, and natural esteem of work as autonomous factors. Career intrigued as the subordinate variable. The target populace is bookkeeping understudies’ course 20 at the Islamic College of Malang, Muhammadiyah College of Malang, and Maulana Malik Ibrahim College of Malang. The test estimate was decided utilizing purposive inspecting with the characteristics of respondents having passed review course 1 and having gone to an internship program so that 150 respondents were gotten. The speculation was tried through a few measurable analyzes counting graphic insights, instrument testing, typicality test, classical suspicion test, numerous straight relapse examination, and speculation testing utilizing SPSS form 25. The discoveries appeared that the factors sexual orientation, internship involvement, subjective standards, and inborn esteem work includes a noteworthy impact on bookkeeping students intrigued in seeking after a career as an open bookkeeper. Keyword: Gender, internship experience, subjective norms, and intrinsic value of work.